Mấy ý kiến xung quanh tục thờ Thành Hoàng ở Hàn tộc và Việt tộc - Cao, Thế Trình (Trường Đại học Đà Lạt, 2012)
On the basic comparision be tween seong hwang sin ang (theritua Is of worshiping tutelary genies) of Korean and Tín ngưỡng Thành Hoàng (the rituals of worshiping tutelary genies) of Vietnamese, the art icle asserted that , before contacting Chinese (Hán) culture , Vietnamese people and Korean people had had their own worshiping rituals worshiping those that helped protect the community, e.g. the village tutelary deity.